The relative age effect on physical fitness in preschool children. Issue 13 (2nd July 2020) - Cupeiro, Rocío; Rojo-Tirado, Miguel A.; Cadenas-Sanchez, Cristina; Artero, Enrique G.; Peinado, Ana B.; Labayen, Idoia; Dorado, Cecilia; Arias-Palencia, Natalia M.; Moliner-Urdiales, Diego; Vidal-Conti, Josep; Conde-Caveda, Julio; Mora-Gonzalez, Jose; et al.
ABSTRACT: The aim of the present study was to investigate the existence of a relative age effect (RAE) on physical fitness of preschoolers. Anthropometry and physical fitness were assessed in 3147 children (3–5 years old) using the PREFIT battery. Based on the birth year, participants were divided into 3year groups (3-, 4- and 5-years). Within each year group, 4quarter groups were created: quarter 1, preschoolers born from January to March; quarter 2, from April to June; quarter 3, from July to September; quarter 4, from October to December. The MANCOVA analysis revealed a main effect of year group (Wilks' λ = 0.383; F10, 5996 = 369.64; p < 0.001, ηp 2 = 0.381) and of quarter (Wilks' λ = 0.874; F15, 8276.6 = 27.67; p < 0.001; ηp 2 = 0.044) over the whole battery of tests. To the best of our knowledge, this is the first study to report the existence of RAE at the preschool stage. In general, performance improved as the relative age increased (i.e., those born in quarter 1 performed better than those in the other quarters). Individualization strategies should be addressed within the same academic year not only in elementary or secondary years but also in preschoolers.